Strong implicative hyper K-ideals - Young Bae Jun; Kyung Ho Kim; Eun Hwan Roh (International Journal of Mathematics and Mathematical Sciences)
A condition for a strong hyper K-ideal to be a strong implicative hyper K-ideal is given. Homomorphic images and inverse images of strong implicative hyper K-ideals are considered.